Photothermal confocal multicolor microscopy of nanoparticles and nanodrugs in live cells - Nedosekin, Dmitry A. (Drug Metab Rev, 2015)
Growing biomedical applications of non-fluorescent nanoparticles (NPs) for molecular imaging, disease diagnosis, drug delivery, and theranostics require new tools for real-time detection of nanomaterials, drug nano-carriers and NP-drug conjugates (nanodrugs) in complex biological environments without additional labeling. Photothermal (PT) microscopy (PTM) has an enormous potential for absorption-based identification and quantification of non-fluorescent molecules and NPs at a single molecule and 1.4 nm gold NP level. Recently, we have developed confocal PTM providing three-dimensional (3-D) mapping and spectral identification of multiple chromophores and fluorophores in live cells. Here, we summarize recent advances in the application of confocal multicolor PTM for 3-D visualization of single and clustered NPs, alone and in individual cells. In particular, we demonstrate identification of functionalized magnetic and gold-silver NPs, as well as graphene and carbon nanotubes in cancer cells and among blood cells. The potentials to use PTM for super-resolution imaging (down to 50nm), real-time NP tracking, guidance of PT nanotherapy and multiplex cancer markers targeting, as well as analysis of nonlinear PT phenomena and amplification of nanodrug efficacy through NP clustering and nanobubble formation are also discussed.